Elastic Halochromic Fiber as a Reversible pH Sensor. Issue 3 (10th February 2021) - Hong, Taekuk; Choi, Yong Kyu; Lim, Taekyung; Seo, Keumyoung; Jeong, Sang‐Mi; Ju, Sanghyun
Abstract: Wearable textile colorimetric sensors are extremely effective for expressing danger or warning, as they are non‐invasive and exhibit easily recognizable color changes. However, unlike conventional sensors, these devices are actually worn by individuals and should, therefore, not only detect hazardous chemicals in real time but also maintain the reversibility, durability, and stability of color change upon exposure to sweat, repetitive movement, and environments involving continuous exposure to chemical substances. Herein, a halochromic fiber maintaining excellent pH sensing properties upon continuous exposure to chemical and physical stimuli is fabricated. The fiber surface is rendered hydrophobic by phosphonic acid treatment, and a composite pH indicator dye capable of simultaneously detecting acids and bases is embedded into the fiber pores. The halochromic fiber could accurately detect pH while maintaining a clear color transition even after repeated changes in the acidic–basic environment, returning to the neutral state within several seconds after termination of exposure to the test solution. Thus, the presented technique allows one to significantly improve the reversibility, durability, and stability of color change—a problem faced by conventional wearable sensors—and, thus, greatly contributes to the development of halochromic textile sensors applicable to real‐life work environments. Abstract : The halochromic fiber could accurately detect pH while maintaining a clear color transition even after repeated changes in the acidic–basic environment, returning to the neutral state within several seconds after termination of exposure to the acidic–basic solution. The halochromic fiber maintains excellent pH sensing properties upon continuous exposure to chemical and physical stimuli.